Pengaruh ROA, ROE, NPM dan Modal Kerja terhadap Return Saham pada Perusahaan Transportasi di BEI (2019-2023) - Fitriyani M. Rukin; Maria Safitri (MANAJEMEN, 2025)
This study analyzes the influence of financial performance indicators—ROA, ROE, NPM, and Working Capital—on stock returns of transportation companies listed on the Indonesia Stock Exchange during 2019–2023. Using multiple linear regression, the findings indicate that ROA and ROE significantly and positively affect stock returns, while NPM has no significant effect. Conversely, Working Capital shows a negative significant effect.